2013
DOI: 10.1371/journal.pone.0066026
|View full text |Cite
|
Sign up to set email alerts
|

A Simple Method for Purification of Vestibular Hair Cells and Non-Sensory Cells, and Application for Proteomic Analysis

Abstract: Mechanosensitive hair cells and supporting cells comprise the sensory epithelia of the inner ear. The paucity of both cell types has hampered molecular and cell biological studies, which often require large quantities of purified cells. Here, we report a strategy allowing the enrichment of relatively pure populations of vestibular hair cells and non-sensory cells including supporting cells. We utilized specific uptake of fluorescent styryl dyes for labeling of hair cells. Enzymatic isolation and flow cytometry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 39 publications
0
16
1
Order By: Relevance
“…In order to identify interaction partners of otoferlin, we used E18 vestibular maculae of the chicken utricle, each containing more than 20000 hair cells for affinity purification of otoferlin. Most vestibular hair cells are functional at this late embryonic age ( Goodyear et al, 1999 ), and utricles can be dissected relatively quickly in larger numbers ( Herget et al, 2013 ). Membrane proteins of 60 avian utricular maculae were solubilized with octyl-β- D -glucopyranoside ( Kim et al, 2004 ) and otoferlin and its potential binding partners were purified using the monoclonal anti-chicken otoferlin antibody HCS-1 ( Goodyear et al, 2010 ), immobilized to magnetic dynabeads.…”
Section: Resultsmentioning
confidence: 99%
“…In order to identify interaction partners of otoferlin, we used E18 vestibular maculae of the chicken utricle, each containing more than 20000 hair cells for affinity purification of otoferlin. Most vestibular hair cells are functional at this late embryonic age ( Goodyear et al, 1999 ), and utricles can be dissected relatively quickly in larger numbers ( Herget et al, 2013 ). Membrane proteins of 60 avian utricular maculae were solubilized with octyl-β- D -glucopyranoside ( Kim et al, 2004 ) and otoferlin and its potential binding partners were purified using the monoclonal anti-chicken otoferlin antibody HCS-1 ( Goodyear et al, 2010 ), immobilized to magnetic dynabeads.…”
Section: Resultsmentioning
confidence: 99%
“…A recent proteomic analysis comparing vestibular hair cells with non-sensory cells found that approximately 50% of the hair cell enriched proteins are involved in protein trafficking, while just 4% of the proteins enriched in non-sensory cells are associated with intracellular transport (Herget et al, 2013). The most abundant protein that Herget et al identified in their hair cell fraction was Otoferlin, an essential regulator of synaptic vesicle exocytosis and neurotransmitter release in hair cells (Dulon et al, 2009).…”
Section: Critical Molecular Processesmentioning
confidence: 99%
“…At present, only a small proportion of the hair cell transcriptome has been identified. For example, various array- based methods (McDermott et al, 2007;Hertzano et al, 2011;Sinkkonen et al, 2011) and proteomic studies (Herget et al, 2013;Shin et al, 2013) have identified a few hundred hair cell markers. Therefore, we implemented a filter on the entire list of 3661 genes that required a Ͼ2-fold expression drop at 0 -24 h and a relative recovery by 168 h. This resulted in a list of 526 genes (some examples are shown in Table 1), within which were our 32 hair cell "sentinel" genes.…”
Section: Identifying Components Of the Hair Cell Transcriptomementioning
confidence: 99%